InterPARES Project on the Electronic Records Management and Team Turkey Activities - Külcü, Özgür; Çakmak, Tolga (Information World, 2009)
InterPARES Project was started in 1999 and it has three stages. Today, InterPARES 3 Project studies are carried with 15 teams that contain Turkey. While the conceptual and methodological findings of InterPARES 1 and InterPARES 2 (InterPARES 1/ 1999-2001; InterPARES 2/ 2002-2007) are equally applicable to larger and smaller organizations and programs, archives with limited resources, which often have the greatest need for assistance, will result in the outcomes of the research difficult to apply without specific directions on how to move forward. This research project will translate the theory and method of digital preservation drawn from research to date into concrete action plans for existing bodies of records that are to be kept over the long term by archives and archival record units within organizations endowed with limited resources.
Keywords: Electronic records management; InterPARES Project; Turkey